Prevalence of Cardiovascular Diseases Risk Factors among Border Guard Bangladesh Personnel - Wahab, Md Abdul; Rahman, Md Mustafizur; Razzak, Md Abdur; Rahman, Md Habibur; Zafreen, Farzana (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: The prevalence of cardiovascular diseases (CVDs) is rapidly increasing at an alarming rate worldwide and is currently considered as the leading cause of death. List of both modifiable and non-modifiable risk factors for CVDs are long and no particular group of people is immune from it. Objectives: To determine the prevalence of CVDs risk factors among the Border Guard Bangladesh (BGB) personnel. Materials and Methods: This descriptive cross-sectional study was conducted from January to December 2017 among 1225 BGB personnel aged over forty years and working in Chattogram Hill Tracts (CHT) of Bangladesh. Respondents’ socio-demographic characteristics, health history and physical activities were collected in a pre-tested questionnaire. Blood pressure (BP), anthropometric and laboratory parameters were measured and categorized as per the standard procedure. Results: Study subjects’ positive family history of hypertension (HTN), ischemic heart disease, diabetes mellitus and bronchial asthma was 9.6%, 1.8%, 7.9% and 14.2% and positive personal history was 11.5%, 2.5%, 9.7% and 5.6% respectively. A positive history of smoking, using Jorda, Gull and extra salt was 20.4%, 8.9%, 3.5% and 16.3% respectively. Among the respondents by systolic BP; elevated BP, stage1 and stage2 HTN was found 41.5%, 17.6% and 5.7% and by diastolic BP it was 20.9%, 10.3% and 6.8% respectively. Nutritional status by body mass index was; obese 1.2% and overweight 52.5% but by waist-hip ratio only 1.7% was obese. Diabetic and pre-diabetic by ‘Fasting plasma glucose’ was 7.5% and 16% in contrary to ‘Oral glucose tolerance test’ was 8.7% and 17.5% subjects respectively. Very high, high and borderline high total cholesterol was found among 5.5%, 15.1% and 37.8%; triacylglycerol was 2.2%, 32.7% and 29.6% and LDL-cholesterol was 6.5%, 8.5% and 22.7% respondents respectively. HDL-cholesterol was found low in 12.9% study subjects. Conclusion: High prevalence of both modifiable and non-modifiable risk factors of CVDs was found among BGB members. Targeted interventions are needed to reduce modifiable risk factors and prevent CVDs. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 29-32